Effect of Defoliation on Growth and Tracheid Characters of Pinus caribaea Seedlings - Bhatnagar, H. P.; Talwar, K. K. (Indian Forester, 1977)
Experiments were conducted with the seedlings of Pinus caribaea to study the effect of defoliation on growth and tracheid characters. In general, the defoliation of upper half of the stem brings about more retardation of radial growth as well as height growth than the defoliation of lower half of the stem. This is true also for the tracheid length and tracheid wall thickness. No distinction in the effect of defoliation of upper half or lower half have been obtained in the case of tracheid or lumen diameter. In the case of dry matter production, it is indicated that higher degree of defoliation retard the production more than lower degree of defoliation Here also the defoliation of lower portion is less effective in retardation of dry matter than the defoliation of upper half. Mineral and holocellulose contents have CoULwed similar trend as that followed by dry matter.